Kids ScreenTime: Mobile Application for Internet Usage Monitoring - Zakaria, Nur Haryani; Paneerselvam, Serlena; Mat Aji, Zahurin; Katuk, Norliza; Omar, Mazni; Abd Manaf, Abdul Razak (Multidisciplinary Applied Research and Innovation, 2023)
The pandemic of Covid-19 transforms our daily life by bringing new norms which makes Internet as an essential component in our everyday routine. With regard to this, both parents and kids are also fully depended on the Internet for their online classes, assessments and for work purposes. Unfortunately, the kids lose track of time while accessing Internet, which seem to be more entertaining. Currently, majority parents were found struggling to monitor their kid’s Internet usage. Thus, this project proposes a mobile application for Internet usage monitoring aiming to assist parents who are concern on their kid’s Internet usage. This project involved Rapid Application Development (RAD) methodology for developing the mobile application. The outcomes of this project are beneficial for parents not only for monitoring purposes but also as a training platform for their kids during this transition period.